TECHNOLOGICAL PROPERTIES OF CHILLED BEEF OF VARIOUS COLOR CLASSES - I, V. Kozyrev; T. M. Mittelstein; V. A. Pchelkina; A. B. Lisitsyn (Теория и практика переработки мяса, 2017)
Technological properties were studied for chilled beef of different classes concerning the color of muscle tissue obtained from Hereford (beef cattle) and White-and-Black (beef and dairy cattle) breeds. The color of Longissimus dorsi muscle in CIELab units wasexamined using Konica Minolta CM‑2300d spectrophotometer. Based on the measurement of muscle tissue color, the classification was carried out according to color standards. According to differences in color, beef was sorted into three groups using color standards and L*, a*, b* values: Class 1 (41.41, 22.16, 18.46 in average), Class 4 (34.75, 22.0, 14.0 in average), Class 5 (28.92, 13.10, 9.24 in average). In a conveyor environment, pH was also measured 24 hours after slaughter: 5.28 to 5.36 for Class 1, 5.59 to 5.60 for Class 4, 6.50 to 6.51 for Class 5. In beef samples (n = 15), the following laboratory parameters were determined: water holding capacity (WHC), moisture loss during heat treatment, structural and mechanical properties, microstructural properties. To establish the relationship between color and technological properties of beef, the L* (lightness) parameter was chosen, which was the most different between the samples. Correlations between L* (lightness) and technological properties were established: negative with pH (0.95) and with water holding capacity (0.92), positive with moisture loss during thermal treatment (0.99) and with shear force (0.96).